Exploring Factors for Achieving Successful Educational Attainment among Chinese Doctoral Students in the United States - Wu, Shiyou; Wu, Qi; Wei, Xiaojiang; Bledsoe, Sarah E.; Ansong, David (Journal of International Students, 2020)
This study aims to understand the pathways of successful educational attainment (SEA) among Chinese students who are pursuing doctorate degrees in the United States. An exploratory qualitative approach was used to identify the factors of SEA. Based on the in-depth interviews of nine participants, we found common factors of SEA at the micro level include individuals’ personalities, visions/dreams of achieving SEA, and interest about study/research; mezzo level factors include important peoples’ help, satisfaction with teachers, previous education experiences in China, and home environment; whereas at the macro level, not many participants mentioned that their SEA was due to Chinese social policy. Overall, most participants mentioned that being lucky was an important factor of SEA.